Multi-isotopic evidence reveals the emergence of a cosmopolitan community at the Luistari cemetery in Eura, Finland, during the early Medieval period (600–1130 CE) - Danielisová, Alžběta; Nordfors, Ulla; Kertes, Samuel; Wessman, Anna; Ackerman, Lukáš; Oinonen, Markku; Etu-Sihvola, Heli; Arppe, Laura (Springer Science and Business Media LLC, 2025)
This study examines the role of the Eura region as a nexus linking the inland with Baltic Sea trade routes. Luistari cemetery, spanning from the early Merovingian to Medieval periods, provides key insights into SouthWestern Finland's socioeconomic structure and communication networks. Despite its significance, this burial community's chronological dynamics and regional role remain poorly understood. Using multi-isotopic evidence contextualised with archaeological data, this research explores mobility and subsistence patterns among Luistari's population. By delineating the bioavailable strontium range in the Eura region, the study assesses the local burial community's mobility dynamics across various chronological phases. Identification of long-and short-distance migrants, discerned through strontium and carbon isotopes in conjunction with archaeological context, enhances understanding of Luistari within the regional and Circum-Baltic framework. Multi-isotopic evidence further aids in grasping local development within environmental and climatic contexts. Analysis of the strontium isotopic data patterns, combined with carbon and nitrogen, sheds light on settlement locations and subsistence strategies of the Luistari population. Notable transformations during the Viking I period (800-880 CE), marked by the establishment of a "founding" community, and shifts in dietary and migratory patterns in periods V II-III (880-1000 CE), indicate stabilisation of the local socioeconomic conditions. Period V IV (1000-1070 CE) reveals connections, both maritime and continental, as the local community integrates into long-distance communication networks. The Final Period (1070-1130 CE) then shows only limited signs of mobility. The data suggest varied mobility patterns over the long-term development of the local community coupled with visibly changing subsistence strategies.